Hole‐Transfer Dependence on Blend Morphology and Energy Level Alignment in Polymer: ITIC Photovoltaic Materials. Issue 3 (4th December 2017) - Eastham, Nicholas D.; Logsdon, Jenna L.; Manley, Eric F.; Aldrich, Thomas J.; Leonardi, Matthew J.; Wang, Gang; Powers‐Riggs, Natalia E.; Young, Ryan M.; Chen, Lin X.; Wasielewski, Michael R.; Melkonyan, Ferdinand S.; Chang, Robert P. H.; et al.
Abstract: Bulk‐heterojunction organic photovoltaic materials containing nonfullerene acceptors (NFAs) have seen remarkable advances in the past year, finally surpassing fullerenes in performance. Indeed, acceptors based on indacenodithiophene (IDT) have become synonymous with high power conversion efficiencies (PCEs). Nevertheless, NFAs have yet to achieve fill factors (FFs) comparable to those of the highest‐performing fullerene‐based materials. To address this seeming anomaly, this study examines a high efficiency IDT‐based acceptor, ITIC, paired with three donor polymers known to achieve high FFs with fullerenes, PTPD3T, PBTI3T, and PBTSA3T . Excellent PCEs up to 8.43% are achieved from PTPD3T:ITIC blends, reflecting good charge transport, optimal morphology, and efficient ITIC to PTPD3T hole‐transfer, as observed by femtosecond transient absorption spectroscopy. Hole‐transfer is observed from ITIC to PBTI3T and PBTSA3T, but less efficiently, reflecting measurably inferior morphology and nonoptimal energy level alignment, resulting in PCEs of 5.34% and 4.65%, respectively. This work demonstrates the importance of proper morphology and kinetics of ITIC → donor polymer hole‐transfer in boosting the performance of polymer:ITIC photovoltaic bulk heterojunction blends. Abstract : Three high‐fill‐factor OPV polymers, PTPD3T, PBTI3T, and PBTSA3T are paired with the high performance acceptor, ITIC . A maximum power conversion efficiency of 8.43% is achieved with PTPD3T:ITIC blends due primarily to increased short‐circuit current density. Ultrafast hole‐transfer from ITIC to PTPD3T is observed by femtosecond transient absorption measurements due to the superior blend morphology and improved charge transport versus PBTI3T:ITIC and PBTSA3T:ITIC blends.